Attentional bias in change detection - Bubić, Andreja (Array, 2008)
Summary: Although change detection constitutes an important and pervasive process in our everyday lives, phenomena such as change blindness show that we are quite limited in our ability to notice even large changes in visual scenes. This process is greatly dependent on attention, so change blindness often occurs when attention is diverted from the changing object. This study explores the efficiency of change detection for stimuli that employ our attentional resources in different ways. A flicker paradigm is used to test how top-down and bottom-up attentional biases affect the change detection process and how they interact when jointly present within a task. Our results indicate the influence of top-down attentional effect reflected in the more efficient change detection in conditions where changes occurred in the set of stimuli participants were employing at the time. The effect of bottom-up attentional bias on the efficiency of change detection was not statistically significant